Host Inflammatory Biomarkers of Disease Severity in Pediatric Community-Acquired Pneumonia: A Systematic Review and Meta-analysis - Fernandes, Catarina D. (2019)
C.D.F. is supported by scholarship from the Fundação de Amparo à Pesquisa da Bahia (FAPESB). M.B.A. and P.M. receive a fellowship from the Fundação de Amparo à Pesquisa da Bahia (FAPESB). M.Cl.M.C. and C.L.V. are supported by CNPq (Brazilian National Council for Scientific and Technological Development). M.Ca.M.C. receives a scholarship from the Faculdade de Tecnologia e Ciências (FTC). B.B.A. and K.F. are supported by the intramural research program of FIOCRUZ. B.B.A. receives a senior fellowship from CNPq.